Introduction - Carastathis, Anna; Kouri-Towe, Natalie; Mahrouse, Gada; Whitley, Leila (Refuge, 2018)
While the declared global “refugee crisis” has received considerable scholarly attention, little of it has focused on the intersecting dynamics of oppression, discrimination, violence, and subjugation. Introducing the special issue, this article defines feminist “intersectionality” as a research framework and a no-borders activist orientation in trans-national and anti-national solidarity with people displaced by war, capitalism, and reproductive heteronormativity, encountering militarized nation-state borders. Our introduction surveys work in migration studies that engages with intersectionality as an analytic and offers a synopsis of the articles in the special issue. As a whole, the special issue seeks to make an intersectional feminist intervention in research produced about (forced) migration.